Informative EST-SSR markers for genotyping and intraspecific differentiation of Brassica oleracea var. capitata L. - M. N. Shapturenko; T. V. Pechkovskaya; S. I. Vakula; A. V. Jakimovich; Yu. M. Zabara; L. V. Khotyleva (Вавиловский журнал генетики и селекции)
Brassica oleraceae var. capitata L. is characterized by a high level of intraspecific heterogeneity due to some biological features that cause difficulties for breeding creating genetically homogenous forms and maintaining their genetic purity. Microsatellites (SSR) are highly polymorphic markers of plant genomes and represent one of the most effective tools for assessing genetic polymorphism. Among microsatellites, EST-SSR are most interesting, because they are directly linked to the expressed sequences and for that reason are widely used for analysis of genetic diversity and population structure. In this work, we studied the effectiveness of the use of transferable EST-SSR markers for both analyzing white cabbage diversity and genotyping pure lines. As a result, 15 microsatellite loci were characterized for the information content, allelic frequencies and heterogeneity levels. The effective multiallelic markers (Bo20TR, BoDCTD4, BoPC34, BoPLD1, BoCalc, BoPC15) with high information content (PIC > 0.7) that could be successfully used for analysis of inter- and intravarietal polymorphism in B. oleracea var. capitata were identified. It has been shown that intervarietal polymorphism expressed as the allelic diversity of EST SSR loci greatly facilitates varietal identification and typing of individual plants for breeding purposes. Based on the SSR-evaluation and subsequent clustering, the genetic structure of the breeding collection was identified, which showed that most experimental forms, in spite of different origin, have a common ancestral genetic basis. The identified donors of rare alleles could potentially be a source of valuable genetic segregation for further B. oleracea breeding improvement.